KUFR DALAM PERSPEKTIF HADIS - Abidin, Zainal (Institut Agama Islam Negeri (IAIN) Palu, 2008)
Kufr is often considered an antithesis of imÃ¢n. In the mean time, imÃ¢n is the fundamental part of Islamic teaching. Nevertheless, as far as the sources of Islamic teaching are concerned, the term kufr cannotÂ necessarily be graspedÂ asÂ disbelief in Allah (God). InÂ someÂ hadÃ®ths (the prophetâs traditions), we find some terms of kufr that do not indicate disbelief in AllÃ¢h at all. Even, some merely indicate disobedience of the Muslims in performing their Islamic teachings, such asÂ Â performing salÃ¢t. Based on this, this article deals with kufrÂ from the hadÃ®th perspective.Kata Kunci : kufr, perspektif hadis, dosa besar